Interpreting Laww?mah in Qs. Al-Qiy?mah (75) Verse 2: A Semiotic Reading Using Roland Barthes' Theory - Idris, Muhammad; Qotadah, Hudzaifah Achmad; Achmad, Adang Darmawan (Pusdikra Publishing, 2025)
This study undertakes a critical re-examination of the interpretation of the term al- laww?mah in verse 75:2 of S?rat al-Qiy?mah, traditionally understood to signify reprehensible desires or internal moral impulses. Employing Roland Barthes’ semiotic framework, the research conducts a qualitative descriptive analysis to uncover the term’s layered semantic and conceptual significations within the Qur’anic text. The findings yield two pivotal contributions: First, at the semantic level, al-laww?mah transcends mere moral failings to encompass individuals who persistently engage in deliberate wrongdoing despite conscious awareness of their ethical transgressions. Second, within Barthes’ mythic system, al-laww?mah emerges as a symbol of moral hypocrisy, embodying an existential tension between idealized ethical principles and sinful praxis. By synthesizing classical Qur’anic exegesis with modern semiotic theory, the study repositions al-laww?mah as a complex ethical construct, while illuminating its implications for contemporary discourses on moral accountability and spiritual integrity. These insights challenge reductive interpretations of the term, advancing a nuanced understanding of its socio-ethical resonance and underscoring its relevance to interdisciplinary dialogues in religious studies, semiotics, and moral philosophy.